2020
DOI: 10.1080/15374416.2020.1815207
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Understanding and Addressing Mental Health among LGBTQ Youth

Abstract: 1 A quick note on language; I use "LGBTQ" and "sexual and gender minority" interchangeably, intentionally, and in variation (e.g., "sexual minority" or "LGB" and "gender minority") to reflect differences across study samples and measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 119 publications
(147 reference statements)
2
40
0
Order By: Relevance
“…Research on the experiences of LGBTQ youth has primarily focused on disparities and deficits in their health and social capital (Fish, 2020 ; Fish et al, 2020a ). However, resilience is a core feature of the minority stress model (Meyer, 2015 ).…”
Section: Minority Stress and Youth Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Research on the experiences of LGBTQ youth has primarily focused on disparities and deficits in their health and social capital (Fish, 2020 ; Fish et al, 2020a ). However, resilience is a core feature of the minority stress model (Meyer, 2015 ).…”
Section: Minority Stress and Youth Resiliencementioning
confidence: 99%
“…Unfortunately, evidence-based programs supporting LGBTQ youths’ health, wellbeing, and positive development are limited and biased towards individual therapeutic and pharmacological treatment (Coulter et al, 2019 ; Fish, 2020 ). LGBTQ youth also experience barriers to community-based care (e.g., safety concerns, lack of competent providers).…”
mentioning
confidence: 99%
“…However, though Erikson categorizes the adolescent stage as a stage for identity development, one considers whether the narrative development of LGBTQ identity spans beyond the adolescent stage of psychosocial development. Parmenter et al (2020b) sought to understand identity development amongst young adults and found that, though participants were 20-25 years old therefore categorized as young adults in Erikson's intimacy versus isolation stage of development (Erikson, 1982), findings highlighted LGBTQ young adults' experiences of identity conflict and exploration. LGBTQ young adults expressed identity consolidation and conflicts in integrating their LGBTQ identity across their lives (Wagaman et al, 2016;Parmenter et al, 2020b).…”
Section: Erik Erikson's Stages Of Psychosocial Developmentmentioning
confidence: 99%
“…Therefore, with Erikson's identity versus role confusion stage, my identity development had finished after I consolidated my LGBTQ identity. Logically, I would move toward Erikson's young adulthood psychosocial stage of development, intimacy versus isolation, defined as moving toward achieving healthy, fulfilling relationships (Erikson, 1980(Erikson, , 1982Kacerguis and Adams, 1980;Gold and Rogers, 1995;Starks et al, 2017). On the contrary, when identity development is understood through an intersectional perspective, the lack of ethnic identity consolidation with my LGBTQ identity is indicative that my identity development is incomplete.…”
Section: Subtheme 23: Reactions To Coming Outmentioning
confidence: 99%
See 1 more Smart Citation